2022
DOI: 10.21037/jss-22-4
|View full text |Cite
|
Sign up to set email alerts
|

National trends in the utilization of lumbar disc replacement for lumbar degenerative disc disease over a 10-year period, 2010 to 2019

Abstract: Background Lumbar fusion (LF) is commonly performed to manage lumbar degenerative disc disease (LDDD) that has failed conservative measures. However, lumbar disc replacement (LDR) procedures are increasingly prevalent and designed to preserve motion in carefully selected patients. Methods A retrospective cohort study was performed using the National Inpatient Sample (NIS), queried from 2010 to 2019 to identify patients undergoing single and double-level LF or LDR with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…In the paper entitled “ National trends in the utilization of lumbar disc replacement for lumbar degenerative disc disease over a 10-year period, 2010 to 2019 ”, Upfill-Brown et al conducted a retrospective cohort study using population-based administrative data from the National Inpatient Sample in the United States ( 1 ). Authors aimed to determine national trends in lumbar disc replacement and lumbar fusion procedures and investigated the association between surgery type and hospitalization cost, length of stay, non-home discharge destination and complications during initial hospitalization after surgery.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the paper entitled “ National trends in the utilization of lumbar disc replacement for lumbar degenerative disc disease over a 10-year period, 2010 to 2019 ”, Upfill-Brown et al conducted a retrospective cohort study using population-based administrative data from the National Inpatient Sample in the United States ( 1 ). Authors aimed to determine national trends in lumbar disc replacement and lumbar fusion procedures and investigated the association between surgery type and hospitalization cost, length of stay, non-home discharge destination and complications during initial hospitalization after surgery.…”
mentioning
confidence: 99%
“…Authors aimed to determine national trends in lumbar disc replacement and lumbar fusion procedures and investigated the association between surgery type and hospitalization cost, length of stay, non-home discharge destination and complications during initial hospitalization after surgery. They found that the frequency of lumbar disc replacement surgeries decreased between 2010–2013 and remained constant until a slight increase occurred in 2019 ( 1 ). Upfill-Brown et al also showed, after propensity score matching, lumber disc replacement patients had significantly lower complication rates, incurred fewer hospital costs and experienced a significantly shorter length of hospital stay than lumbar fusion patients ( 1 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations